THE SIGNIFICANCE OF LIPID METABOLISM DISORDERS IN THE BLOOD AND SKIN OF PATIENTS WITH PSORIASIS IN THE PATHOGENESIS OF DERMATOSIS - Ghazi Alkammaz, Ali Mohammed (The Ukrainian Scientific Medical Youth Journal, 2017)
The etiology of psoriasis continues to remain unsettled, and issues of the pathogenesis of this dermatosis are also not fully resolved. The analysis of lipid metabolism disorders in the blood and skin of patients with psoriasis, established at the present stage, indicates their importance in the pathogenesis of this dermatosis. At the same time, taking into account the wave-like recurrent course of psoriasis and the existence of autumn-winter, spring-summer and offseason (mixed) types of dermatosis, there remain unsolved questions of the influence of the features of lipid spectrum indexes in the body of psoriasis patients in the development of clinical exacerbations of dermatosis in different seasons of the year. Uncertainty is also the possibility of a correlation relationship between the degree and nature of imbalance in the level of the lipid spectrum in the blood and skin of patients with psoriasis with the severity of the clinical course of dermatosis. Further in-depth study of lipid metabolism in the body of patients with psoriasis involving new immunopathohistochemical techniques will contribute to the development of an improved complex individualized therapy and broadening the understanding of the pathogenesis of this dermatosis.